Monitoring of transfer and internalization of Escherichia coli from inoculated knives to fresh cut cucumbers (Cucumis sativus L.) using bioluminescence imaging - Yeting Sun (Nature Portfolio, 2021)
Abstract Slicing may cause the risk of cross-contamination in cucumber. In this study, knife inoculated with Escherichia coli (E. coli) was used to cut cucumbers, bioluminescence imaging (BLI) was used to visualize the possible distribution and internalization of E. coli during cutting and storage. Results showed that the initial two slices resulted in greater bacterial transfer. The bacterial transfer exhibited a fluctuating decay trend, E. coli was most distributed at the initial cutting site. The contaminated area on the surface of cucumber slices decreased during the storage period, which can be attributed to the death and internalization of E. coli. The maximum internalization distance of E. coli was about 2–3 mm, and did not further spread after 30 min from inoculation. Hence, our results provide useful information for risk management in both home and industrial environment.